Founding brothers : the revolutionary generation - Ellis, Joseph J. (New York : Vintage Books, 2002)
An analysis of the intertwined careers of the founders of the American republic documents the lives of John Adams, Aaron Burr, Benjamin Franklin, Alexander Hamilton, Thomas Jefferson, James Madison, and George Washington.
Includes bibliographical references (p. 249-278) and index.
Keywords: Statesmen -- United States -- Biography -- Anecdotes; Presidents -- United States -- Biography -- Anecdotes; United States -- History -- 1783-1815 -- Anecdotes; United States -- Politics and government -- 1783-1809 -- Anecdotes